Simulation of grid connected THIPWM-three-phase inverter using SIMULINK - Younis, M.A.A.; Rahim, N.A.; Mekhilef, Saad (2011)
This paper presents a grid connected system. Three phase DC-AC inverters used to convert the regulated DC power to AC power suitable for grid connection. Third harmonic injection PWM (THIPWM) was employed to reduce the total harmonic distortion (THD) and for maximum use of the voltage source. the accurate generation of THIPWM minimize the THD and make the inverter suitable for grid connection, by synchronizing the inverter voltage with the grid voltage. The application of THIPWM to inverter increases efficiency of the inverter. Simulation results validate the developed model and the proposed system.